Analysis of the Utilization of Artificial Intelligence (AI) Technology in the Implementation of the Merdeka Belajar Curriculum - Kaneishia, Jiya (Trigin Institute, 2025)
This study analyzes the utilization of Artificial Intelligence (AI) technology in the implementation of the Merdeka Belajar curriculum in Indonesia. The emergence of AI in education has been recognized globally as a catalyst for personalized learning, efficiency, and innovation, yet its integration within the Indonesian context remains underexplored. Drawing on a qualitative descriptive approach, this research examines the current level of AI adoption, teachers’ and students’ perceptions, as well as the success stories, challenges, and barriers that shape its implementation. The findings reveal that AI aligns strongly with the principles of Merdeka Belajar, particularly in promoting independent learning, creativity, and critical thinking. Teachers view AI as a tool that reduces administrative tasks and supports differentiated instruction, while students appreciate its role in providing personalized feedback and learning pathways. However, significant obstacles persist, including infrastructural inequalities, low digital literacy, policy fragmentation, and ethical concerns related to data privacy and algorithmic bias. Comparison with previous studies shows that while global literature emphasizes the transformative potential of AI, the Indonesian context highlights localized barriers that require urgent attention. This research concludes that AI can play a vital role in advancing Merdeka Belajar, provided that its adoption is supported by stronger infrastructure, comprehensive training, clear policies, and ethical guidelines.